Impact of BMI on Erythrocyte Sedimentation Rate and C-Reactive Protein in Patients Without A Rheumatic Autoimmune Disorder: A Medical Record Analysis - Carroll, Matthew B. (British Journal of Healthcare and Medical Research, 2023)
Objective: Obesity is an inflammatory condition associated with arthralgias. Erythrocyte Sedimentation Rate (ESR) and C-Reactive Protein (CRP) measure systemic inflammation. Increasing body mass index (BMI) could increase ESR and CRP in patients with nonspecific arthralgias. Methods: Medical record analysis of 1,185 clinic encounters was performed. Relationship between BMI with ESR and CRP and differences compared among three groups (Group 1: BMI ≤ 29.9 kg/m², Group 2: BMI ≥ 30.0 kg/m² but ≤ 39.9 kg/m², and Group 3: BMI ≥ 40.0 kg/m²). Results: Mean age 56.8 (± 14.1) years with a female predominance (82.2%) and age 50 years (71.2%). Weak positive correlation with ESR (r = 0.147, p < 0.0001) with no relationship with CRP (r = 0.042, p = 0.151). Relationship with ESR stronger for age under 50, female gender, and Caucasian ethnicity. Relationship with CRP stronger for age under 50, female gender. Mean ESR higher in Group 3 (37.9 (95% Confidence Interval (CI) 35.4 – 40.5) mm/hr). Mean CRP in Group 3 (2.00 (95% CI 1.82 – 2.19) mg/dL) higher than Group 2 but not Group 1. Group 3 mean ESR higher for age under 50, female gender, Caucasian ethnicity. Group 3 mean CRP higher for female gender. Conclusion: Positive correlation between BMI and ESR noted. Mean ESR and CRP higher for Group 3. For ESR, age under 50, female gender, and Caucasian ancestry demonstrated statistically significant differences for Group 3. For CRP, only female gender higher for Group 3.